2018
DOI: 10.36510/learnland.v11i2.965
|View full text |Cite
|
Sign up to set email alerts
|

I Wish, I Wonder, and Everything I Like: Living Stories of Piano Teaching and Learning With Young Children

Abstract: The purpose of my inquiry is to learn more about how young children learn to play the piano through examining my own teaching practice. By using autoethnography as a creative nonfictional form of storytelling, I illustrate my learning journey in search for joyful and meaningful ways of exploring music and piano playing with young beginner students. In writing stories about my learning experiences as a piano teacher, I discuss the importance, value, and need for piano teachers’ autoethnographies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 3 publications
(4 reference statements)
0
1
0
1
Order By: Relevance
“…Among them, the minimum value of the root mean square difference is 0.1962. This comparative result shows that the prediction effect of the fuzzy neural inference system is the most favorable (Ryu, 2018).…”
Section: Evaluation Of the Effect Of College Piano Teaching Based On Aimentioning
confidence: 79%
“…Among them, the minimum value of the root mean square difference is 0.1962. This comparative result shows that the prediction effect of the fuzzy neural inference system is the most favorable (Ryu, 2018).…”
Section: Evaluation Of the Effect Of College Piano Teaching Based On Aimentioning
confidence: 79%
“…Piano education in higher education is beneficial for students to comprehend art, form their own artistic opinions, and develop good music appreciation habits. The polishing of students' minds can be seen as a way to overcome many psychological problems in their growth and lay the foundation for healthy development [17][18]. By providing students with a stage to showcase their individuality, students' desire for communication and expression is well realized, and it also promotes the formation of a healthy campus culture, enabling students to better plan their next academic life according to their developmental needs [19][20].…”
Section: Build a Model Of Piano Teaching In Collegementioning
confidence: 99%
“…Practice has shown that the teaching method under the "micro era" has realized the upgrading of piano professional teaching from teaching concept to evaluation system [4]. Ryu analyzed the problems existing in today's piano teaching classroom and proposes corresponding solutions to these problems [5]. Tese studies on the application of the IoT network in piano teaching are rich, but lack pertinence.…”
Section: Introductionmentioning
confidence: 99%